2015
DOI: 10.1186/s40621-015-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Urban/Rural disparities in Oregon pediatric traumatic brain injury

Abstract: BackgroundTraumatic brain injury (TBI) greatly contributes to morbidity and mortality in the pediatric population. We examined potential urban/rural disparities in mortality amongst Oregon pediatric patients with TBI treated in trauma hospitals.MethodsWe conducted a retrospective study of children ages 0–19 using the Oregon Trauma Registry for years 2009–2012. Geographic location of injury was classified using the National Center for Health Statistics Urban/Rural Classification Scheme. Incidence rates were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 22 publications
1
48
1
Order By: Relevance
“…Many states' PDMP data are inaccessible for research due in part to privacy concerns (Brandeis University 2017). In our experience, the management of the Oregon PDMP by the Public Health Division, a shared interest in veterans' health, and a history of collaboration and partnership between institutions (e.g., Basham et al 2011;Kane et al 2014;Leonhard et al 2015) supported the development of a data use agreement that met both VA and state PDMP program requirements. This included negotiating the details of where and on what information technology system to bring the data together for linkage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many states' PDMP data are inaccessible for research due in part to privacy concerns (Brandeis University 2017). In our experience, the management of the Oregon PDMP by the Public Health Division, a shared interest in veterans' health, and a history of collaboration and partnership between institutions (e.g., Basham et al 2011;Kane et al 2014;Leonhard et al 2015) supported the development of a data use agreement that met both VA and state PDMP program requirements. This included negotiating the details of where and on what information technology system to bring the data together for linkage.…”
Section: Discussionmentioning
confidence: 96%
“…; Leonhard et al. ) supported the development of a data use agreement that met both VA and state PDMP program requirements. This included negotiating the details of where and on what information technology system to bring the data together for linkage.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of rural‐urban disparities related to the incidence of pediatric mTBI is mixed. Oregon Trauma Registry data show higher incidence of TBI is greater among rural‐dwelling than urban‐dwelling children; however, other research has suggested a lower incidence rate of emergency department visits for concussions in rural areas compared to urban areas . It is possible that mTBI is underreported in rural areas, where more limited access to health care, including emergency departments, can contribute to different patterns of health service utilization .…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that many students with more severe concussions and special education needs resulting from TBI do not receive adequate services in school . Whereas it is recognized that providing appropriate academic accommodations and school services to children with concussion is critical for supporting their recovery and development, and for increasing their capacity for higher education and work productivity, barriers to accessing school services such as lack of medical documentation and poor communication between medical professionals and schools are reported to hinder implementation of return to learn (RTL) services …”
mentioning
confidence: 99%